(untitled) (Jagannath University Journal of Science, 2025)
This research investigates at the dynamics of bifurcation in a logistic harvesting model that’s tailored to pond trout populations. The majority of the time, this strategy is employed by pond trout populations. The logistic model accurately portrays the increase of trout populations by taking a variety of parameters into account, including carrying capacity and harvesting rates. Using applied bifurcation theory, researchers examine the effects of varying harvesting intensities on population dynamics and stability. Observational data has helped to identify critical thresholds at which trout populations experience qualitative shifts. These changes allow for oscillatory dynamics and changes in equilibrium points. In order to comprehend the sustainability and long-term consequences of resource extraction on population dynamics, the discussion centers on the Harvesting model’s answers and various recommendations. Due to unsustainable harvesting practices, the described conditions are favorable to a decrease or collapse of the population. By comparing it to other ecological models, the robustness and possible usefulness of the logistic harvesting model are investigated. In order to aid trout populations and maintain ecological balance, this paper aims to educate ecologists and fishery managers on sustainable harvesting techniques. Jagannath University Journal of Science, Volume 11, Number 2, Dec. 2024, pp. 67−85